Testing components of Rothbard’s theory with the current information system - BĂLUŢĂ, Aurelian Virgil (Annals of Spiru Haret University. Economic Series, 2016)
The concept of aggression against property rights of individuals generates a series of developments that allow solutions and options to problems and dilemmas of today’s economy: the dynamics of the tax system, focusing attention on shaping the budget with macro-economic calculations, the protection of competition, and customs policy in the modern era. The confidence in theory in general, especially in economic theory, is based on the logical and methodological validation of scientific reasoning and moral aspects. Transforming the theory into a means of changing the society can only be made when a theory is experimentally validated. The economic theory needs confirmation from specialized disciplines such as statistics and accounting. It is possible and necessary for the advantages of radical liberal thinking to be reflected in every company’s bookkeeping and in public statistics. As an example, the paper presents the way some components of Rothbard’s theory are reflect in the accounting and statistics information system.